Is stereotactic radiosurgery under-utilised in the treatment of surgically excisable cerebral metastases?. (October 2013) - Lee, M. K.; Javadpour, M.; Jenkinson, M. D.
Abstract Background/Objective. Brain metastases are a significant cause of morbidity and mortality. Treatment options included surgery, whole brain radiotherapy and stereotactic radiosurgery alone or in combination. There has been a significant increase in stereotactic radiosurgery (SRS) provision in the UK over the last 5 years. We investigated the proportion of surgically resected brain metastases that would be suitable for SRS. Methods. We retrospectively collected data on 116 consecutive patients undergoing surgical resection of brain metastases. Suitable radiological targets for SRS were defined as solid tumours < 30 mm maximum diameter with no hydrocephalus and no symptomatic mass effect. Results. One hundred and two cases (88%) were solitary metastasis and fourteen (12%) had multiple metastases. Median maximum tumour diameter was 34 mm (range: 12–70 mm). Approximately one-third of patients (n = 41) had surgically resected brain metastasis suitable for SRS. Median OS was 7.7 months for those suitable for SRS and 5.4 months for those not suitable for SRS (Fig. 3; Log Rank: P = 0.52). Conclusions. In surgically amenable tumours, day case SRS could also be used in approximately one-third of cases, thereby avoiding craniotomy and reducing length of stay. These data may be useful in planning service provision, and for drawing up business plans for a new SRS services. Nationally agreed guidelines for SRS for brain metastases have been developed and a full health economic analysis warrants further investigation to determine the cost effectiveness of SRS compared to craniotomy.